Numerical Simulation on the Integrated Shallow Water Flow Model - Nor Azlina, Alias; Lariyah, Mohd Sidek (2014)
Even the 2D model has become popular in a few areas of river modelling due to the availability of high-resolution data and development of computer technology, the 1D model has not lost its market. It has long been used in simulating fluvial hydrodynamics and the associated processes such as sediment transport, pollutant dispersion and flooding caused by overtopping or breaching of river banks. In some case of modelling a fluvial flood event, it is still difficult to resolve the problematic river reach in a 2D manner, thus it is desirable to have a 1D component that can deal with the highly dynamic and complex flow hydrodynamics under flood conditions. It is advantageous to have a model solving the fully 1D shallow water equations by the robust Godunov-type scheme so that the unsteady flow in different regimes, including shock-like flow discontinuity, can be reliable simulated (Toro, 2001). The same goes to the solute transport which is closely related to the water quality in shallow water bodies. Solute transport has great impacts on the local environment and ecosystem as it is a common process that take place in rivers, lakes and estuarine. When it is associated with an urban flood event it may also cause potential risk on public health. So, understanding the solute transport processes in shallow flows is thus of fundamental and practical importance to hydraulic and environmental engineering as it provides an essential tool for water quality management, environmental impact assessment and hydraulic design (Falconer, 1992).